ANALISIS TINGKAT PENGARUH ELEVATOR SPEECH-OFFICIAL MOVIE TRAILER DAN BRAND AWARENESS RUMAH PRODUKSI (PH) TERHADAP KEPUTUSAN PEMBELIAN MOVIEGOERS (STUDI KASUS : FILM MAN OF STEEL – WARNER BROS PICTURES DAN IRON MAN 3 – WALT DISNEY STUDIO MOTION PICTURES - Michael Christian; Howard Sarmento Giam; Amelia Suryani (Business Management Journal, 2017)
For almost all sales men, the strategy of time becomes the main key of selling effectiveness. Having appointment in a product’s presentation is oftenly measured by a very short times to deliver. In many cases, delivering the detail of products must be done at a sudden spot and extremely short time where he/she does not imagine before. This needs skill of designing the points of products and how to execute well in order to get the best memorable experience. Entertainment industry especially movie has a very unique on its competition. The development of technology totally delivers big change on how to produce a good film. In recent years, the capability of actor or actress is not the main consideration. We can find many brilliant of them have contributed playing the script however it’s not in line with the moviegers’ responses or the revenue itself. The interest of moviegoers on film sometimes can be seen by various factors. Sound effect, animation technology, pictures editing, original soundtrack, trailers, towards to the name of production house, are numbers of x-factors affecting the moviegoers.This paper intends to describe how the elevator speech-official movie trailer affects the moviegoers. Further this paper also intends to describe how the big production house affects the moviegoers. The analysis is measured by the regression which comes from one hundred respondent involved. The instrument used to collect data is by questionnaire. Most of respondents have the same response that almost all of the indicators have big effects for them. Keywords- Elevator Speech, Brand Awareness, Buying Decision